CityTour Bus Locator and Bus Booking Mobile Application - Chandrasiri , S.; Hettiwatte, S.N. (NSBM Green University, 2018)
The public bus transportation system has the direct impact on economic development of the country. Scheduling, tracking and monitoring of the public bus transportation is one of the major issues for any public transportation sector. Currently, there are many vehicles tracking systems available using Global Positioning Systems (GPS) technology. At present, bus passengers are unable to gather enough information which would lead up to a stress-free bus ride. Under current conditions a passenger has to wait in the bus stand without having any prior idea about the buses. ‘CityTour’ application assists passengers and the conductor to use bus service in more stress-free, well-organized and a suggestive manner. “CityTour”, is the cross-platform application implemented with the sole purpose of addressing these problems a passenger has. The application will predict the next Bus’s arrival time, seat reservation and a rating which will give an indication regarding the quality of the service offered. Bus conductor has a say in whether a passenger gets a seat or not. ‘CityTour’ application enables the “real-time” passenger bus communication that would lead to a better collaboration and make their day-to-day work easier for both the parties.
Keywords: —public bus transportation; estimated time; bus tracking; bus seat reservation.